2015
DOI: 10.1371/journal.pone.0141757
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oral Beta-Hydroxy-Beta-Methylbutyrate (HMB) Supplementation on Physical Performance in Healthy Old Women Over 65 Years: An Open Label Randomized Controlled Trial

Abstract: Although older people are particularly liable to sarcopenia, limited research is available on beta-hydroxy-beta-methylbutyrate (HMB) supplementation in this population, particularly in healthy subjects. In this parallel-group, randomized, controlled, open-label trial, we aimed to evaluate whether an oral supplement containing 1.5 g of calcium HMB for 8 weeks could improve physical performance and muscle strength parameters in a group of community-dwelling healthy older women. Eighty healthy women attending a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(70 citation statements)
references
References 36 publications
1
67
1
Order By: Relevance
“…The cutoffs for dividing the sample into tertiles were 10 and 11 points in men, and 9 and 11 points in women. Since the 4 m walking speed and five times sit-to-stand test are independent predictors of several negative outcomes in older people 24,25 , these parameters were also considered as separate items in this analysis. The cutoffs used for the 4 m gait speed were 0.83 and 0.98 m/s in males, and 0.72 and 0.85 m/s in females; for the five times sit-to-stand test, the corresponding cut-offs were 11.2 and 9.4 in males, and 10.2 and 12.6 s in females.…”
Section: A Physical Performance Testsmentioning
confidence: 99%
“…The cutoffs for dividing the sample into tertiles were 10 and 11 points in men, and 9 and 11 points in women. Since the 4 m walking speed and five times sit-to-stand test are independent predictors of several negative outcomes in older people 24,25 , these parameters were also considered as separate items in this analysis. The cutoffs used for the 4 m gait speed were 0.83 and 0.98 m/s in males, and 0.72 and 0.85 m/s in females; for the five times sit-to-stand test, the corresponding cut-offs were 11.2 and 9.4 in males, and 10.2 and 12.6 s in females.…”
Section: A Physical Performance Testsmentioning
confidence: 99%
“…HMB has since been demonstrated to promote muscle mass, strength, power, or physical performance or reduce skeletal muscle atrophy in elderly subjects [ 40 44 ]. HMB supplementation also prevented the loss of lean mass in a human study of 10 days of bed rest [ 45 ], and has shown similar efficacy in experimental models of cancer cachexia [ 37 , 46 48 ]. On the other hand, several studies, namely in strength-trained athletes, do not support these results and may reflect differences in dose and duration of HMB supplementation or total protein intake [ 49 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…Berton et al ( 23 ) aimed at evaluating whether HP-ONS+HMB given as 1 serving/day for 8 weeks together with a mild fitness program could improve physical performance, muscle strength and body composition parameters. This open labeled RCT was conducted in a group of healthy community dwelling women (aged ≥ 65 years) attending a mild fitness program including mainly aerobic exercise and some resistance exercise.…”
Section: Hmb-enriched Ons In Community Dwelling Older Adultsmentioning
confidence: 99%
“…Recently, HMB has been added to high protein ONS as a means to target muscle loss in context of an optimized nutrition supplement that provides macro and micronutrients to meet the daily requirements of patients with nutritional insufficiencies/deficiencies. Administration of these high protein HMB-enriched oral nutritional supplements (HP-ONS+HMB) has shown promise in helping adults maintain muscle mass and function in hospital and community settings ( 4 , 21 - 23 ). Therefore, the purpose of this review is to summarize and discuss the current evidence that examined nutritional support, mainly through HP-ONS+HMB on muscle function and clinical outcomes in adults with, or at risk of, malnutrition, and both in community and peri-hospitalization settings.…”
Section: Introductionmentioning
confidence: 99%